2021
DOI: 10.1108/itp-04-2020-0182
|View full text |Cite
|
Sign up to set email alerts
|

Does social media usage evoke employees' spirituality? A cross-level moderation model of inclusive leadership

Abstract: PurposeThe purpose of this study is to investigate the impact of social media usage (SMU) and relational energy on employees' workplace spirituality within an organization from a psychological perspective.Design/methodology/approachThis study proposes a research model based on self-determination theory. This research model was tested using a cross-level hierarchical regression analysis. Data were collected from 276 knowledge workers on 39 teams in 37 enterprises in China.FindingsSMU has a significant positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 108 publications
(139 reference statements)
1
7
0
Order By: Relevance
“…In 2020–2022, further progress has been made in research on the impact of employee use of social media on employee attitudes. In terms of positive impact, Zhou and Mou [ 81 ] proposed a cross-level moderation model based on self-determination theory and found that this behavior positively influenced employees’ relational energy and spirituality. Zheng and Davison [ 82 ] concluded that work-related social media use increased employees’ affectionate identification with the team and enhanced the sense of teamwork.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020–2022, further progress has been made in research on the impact of employee use of social media on employee attitudes. In terms of positive impact, Zhou and Mou [ 81 ] proposed a cross-level moderation model based on self-determination theory and found that this behavior positively influenced employees’ relational energy and spirituality. Zheng and Davison [ 82 ] concluded that work-related social media use increased employees’ affectionate identification with the team and enhanced the sense of teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al [ 74 ] found from the self-determination theory three basic psychological needs of employees (i.e., need for competence, need for autonomy, and need for relatedness) influencing employees’ social media use. Zhou and Mou [ 81 ] found that this behavior positively influenced employees’ spirituality based on self-determination theory. Wu et al [ 109 ], based on the transactional theory of stress, found that this behavior generates challenging work stress and hinders work stress, while challenging work stress helps employees to be more effective, and hindering work stress has a negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…When in the heavy workload and under time pressure, expressive suppression can weaken the subjective feeling, and be more prone to emotional exhaustion, which cause employees not easy to gain self-esteem and achievement and make them unable to produce a sense of belonging in the organization ( Zhou and Mou, 2021 ), thus reducing the role immersion. Therefore, they tend to show a negative and indifferent attitude at work, which leads to psychological problems and a strong sense of job burnout, thus affecting job engagement.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The extant studies show that SMU in organizations can play a helpful role in marketing, customer relationship management and information collection, which leads to a positive impact on organizations (Tajudeen et al. , 2018; Zhou and Mou, 2021). However, most organizations seem to be confused regarding the usage of social networking sites during business hours for private purposes in organization management strategies.…”
Section: Discussionmentioning
confidence: 99%